Konspirasi Global : Gerakan dan Aksi - Hamka Hamka; Asep Setiawan; Alfianta Cesario Rizky Maulana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The main topic of this research is Global Conspiracy : Movement and Action. This research is important because significant events in history have been uncovered and re-examined by historians. As a result, revisionist historians have found evidence of a large and powerful global Jewish conspiracy. This research focuses on the global Jewish conspiracy, exploring the issues and investigating what the global Jewish conspiracy is and how it operates. Using conspiracy theory, the researcher analyzes the global Jewish conspiracy. The research employs literature review techniques, gathers data, and then analyzes it using qualitative analysis. From this analysis, the author concludes that the global Jewish conspiracy indeed exists, is large, powerful, and operates on a global scale.